Separation and Recovery of Zn(II) Metal Ions Using Hydroxamic Fatty Acids from the Synthesis of Ketapang Seed Kernel Oil (Terminalia catappa) Immobilized in Bentonite Resin - Renda Suri Pratiwi; Anny Zuliyana; Rudi Purwanto (Institute of Educational, Research, and Community Service, 2024)
Traditional mining methods, such as amalgamation and cyanidation in illegal mining, can generate dangerous metal waste discharge, some of them are Zn(AsO4)2.8H2O and Zn(CN)2. Mining waste containing Zn2+, if discarded in water, will harm sea ecosystem, such as fishes, planktons, and others, because Zn(II) cannot be biodegraded in the body which induce toxic effects. Therefore, it takes a sensitive method and has a high selectivity for the separation of metal ions prior to discharge into the environment. The purpose of this study is to determine the optimum conditions of immobilization FHA-bentonite in the metal ions Zn (II) and determine% recovery of metal ions Zn(II) in the desorption process by the method of immobilization chelating agent by fatty acid hidroksamik of synthesis kernel oil seeds ketapan that has a high chelate. The method is combined with bentonite in order to maximize the separation and concentration of ions Zn (II). From the research results, optimum pH of 5, optimum contact time of 5 hours, and optimum concentration of 120 ppm was obtained, with FHA-bentonite adsorption capacity as much as 10,595 mg/g and recovery result of 103,18 ppm from 103,38 ppm or approximately 99,806%. Therefore it could be concluded that hydroxamic fatty acid can be used as chelating agent to separate and concentrate Zn(II) ion immobilized into bentonite resin.